2021
DOI: 10.1016/j.sapharm.2020.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Provision of clinical pharmacy services during the COVID-19 pandemic: Experiences of pharmacists from 16 European countries

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
114
0
15

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 73 publications
(130 citation statements)
references
References 29 publications
1
114
0
15
Order By: Relevance
“…The expansion of pharmacists’ roles and workforce in the community is also imperative on the face of the COVID-19 pandemic and other infectious diseases of concern [ 50 53 ]. The pandemic has required pharmacy services to offer extended roles in all sectors including continuation of the provision of routine services in the time of hardships and shortages in medicines supply; uptake of novel roles in primary care, hospital and critical care; participation in clinical trials; and provision of education, medicines information; and offering vaccinations [ 50 ]. The findings of this study will be useful in enabling pharmacists’ preparedness and response to current and future pandemic in Saudi Arabia and beyond by harnessing the facilitators and addressing barriers to uptake of novel roles as identified in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The expansion of pharmacists’ roles and workforce in the community is also imperative on the face of the COVID-19 pandemic and other infectious diseases of concern [ 50 53 ]. The pandemic has required pharmacy services to offer extended roles in all sectors including continuation of the provision of routine services in the time of hardships and shortages in medicines supply; uptake of novel roles in primary care, hospital and critical care; participation in clinical trials; and provision of education, medicines information; and offering vaccinations [ 50 ]. The findings of this study will be useful in enabling pharmacists’ preparedness and response to current and future pandemic in Saudi Arabia and beyond by harnessing the facilitators and addressing barriers to uptake of novel roles as identified in this study.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study on the impact of the COVID-19 pandemic on clinical pharmacy practice suggested that pharmacists are being increasingly requested information about dietary supplementation, vitamins, and any options on the shelves that could offer symptom relief and boost immune system. 9 This narrative will aim to discuss global practices and policies in regards to CAM use in COVID-19. A global update will enable understanding of international practices and policies, patient and consumer behaviors, identification of popular CAMs and those tipped for potential benefits, including evidence base, and thereby support counselling and communications by healthcare professionals when patients present for advice.…”
Section: Introductionmentioning
confidence: 99%
“…However, the number of telephone appointments increased over 2.5 folds during the same period [ 6 ]. These drastic changes in the delivery of services in primary care, such as general practices and community pharmacies, have raised concerns with regards to timely equitable access to these services [ 5 , 7 ].…”
Section: Introductionmentioning
confidence: 99%